THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN PREVENTING BULLYING BEHAVIOR AT SMP MUHAMMADIYAH SURAKARTA - Adjie, Pandu Kuncoro (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
Bullying behavior is considered commonplace nowadays, even though the impact is very large on the perpetrators and victims of bullying. Bullying behavior does not only occur in public areas but also educational buildings, not only regarding the use of inappropriate names but also rough touching. Researchers took Muhammadiyah 5 Surabaya Middle School as one of Islamic education to get a solution for handling bullying behavior that should not occur in educational buildings, especially in pre-adolescent or junior high school students. Researchers took a qualitative research method using a descriptive approach through observation of research subjects in a personal way. The results of this approach are translated into a description in the form of a detailed sentence. In this study, the role of the PAI teacher is very influential in solving students who are victims or even perpetrators of bullying at school because religious immunization plays a very important role in reducing bullying behavior in schools. The role of the PAI teacher continues beyond giving theory in the classroom but also assists in the learning process by providing stimulus and motivation. Besides that, the teacher must also set a good example for his students in teaching and behavior inside and outside school.